Study of penetration depth as a function of temperature, in-plane hopping and single particle tunneling in cuprate superconductors - Singh, Mahipal; Dubey, Vikash (International Multidisciplinary Research Journal, 2012)
The present study deals with the study of penetration depth as a function of in-plane hopping matrix element, single particle tunneling between the layers and temperature in bilayer high temperature cuprate superconducting materials. For this purpose, a tight binding bilayer Hubbard Hamiltonian has been considered that includes the in-plane (within CuO2 plane) and out-of-plane interactions. Employing Green’s function technique, the expressions for superconducting order parameters, carrier density and penetration depth are obtained. The numerical analysis shows that in bilayer cuprates the penetration depth depends on in-plane hopping matrix element, single particle tunneling as well as on temperature in an essential way. Finally, we have compared our theoretical results on penetration depth with that of recent experimental results and found to be in qualitative agreement.